Salivary hormones, IgA and performance during intense training and tapering in judo athletes - Papacosta, E.; Gleeson, M.; Nassis, G. P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Judo is a demanding combat sport that incorporates periods of intensified training in order to be able to optimise performance. Therefore, the need for tapering periods during the lead up to competition is essential. The aims of this study were to identify the time-course of change of selected salivary hormones, mucosal immunity, mood state and performance capacity during a 2-week taper in judo athletes, and to examine the diurnal variation in salivary testosterone (sT), cortisol (sC) and IgA (SIgA). Methods Eleven male judo athletes (mean±SD: age 20±6 years; VO2max 57.2±7.2 ml/kg/min; training experience 8.5±4.7 years) completed 5 weeks of training: 1 week of normal training (NORM), 2 weeks of intensified training (INT) and 2 weeks of exponential tapering (TAPER). Five times in total during the study period, subjects completed once per week a vertical and horizontal countermovement jump tests, a grip strength test, a Special Judo fitness test (SJFT), a multistage fitness test (MSFT) and a 3x300-m run test and anthropometric measurement. During this time, subjects also completed questionnaires to assess mood state and muscle soreness. Two daily saliva samples (at 07:00 and 19:00) were collected at the end of each week during NORM and INT and every day during TAPER. Results TAPER resulted in increased morning sT, decreased evening sC, lower muscle soreness and enhanced mood state (all p<0.05). A significant 7.0% improvement in 3x300-m performance time and 6.9% improvement in the vertical countermovement jump were also observed during TAPER. No significant changes were found in the SJFT and MSFT. Enhancements in 3x300-m and vertical jump performance were accompanied by an increased evening sT/C ratio and morning and evening SIgA secretion rate (all p<0.01). A diurnal variation in salivary markers was evident, with the higher values of sT, sC and SIgA absolute concentrations and secretion rate in the morning. Discussion This study has identified that TAPER increased sT, reduced sC and muscle soreness and enhanced mood state in trained judo athletes, and these results are similar to the findings of tapering in cyclists (Zehsaz et al., 2011). The improvements in anaerobic performance and power of lower extremities were concomitant with increased sT/C ratio and enhanced mucosal immunity. This study indicates that changes in salivary hormones, muscle soreness and mood state precede the improvements in performance and mucosal immunity. Furthermore, this study has shown that responses of sT, sC and SIgA absolute concentrations and secretion rate display a diurnal variation with the higher values in the morning, which are in agreement with previous studies in endurance athletes